Intermediate Care Units: A Survey of Organization Practices Across the United States. (May 2020) - Wendlandt, Blair; Bice, Thomas; Carson, Shannon; Chang, Lydia
Purpose: Intermediate care units (IMCUs) represent an alternative care setting with nurse staffing levels between those of the general ward and the intensive care unit (ICU). Despite rising prevalence, little is known about IMCU practices across US hospitals. The purpose of this study is to characterize utilization patterns and assess for variation. Materials and Methods: A 14-item survey was distributed to a random nationwide sample of pulmonary and critical care physicians between January and April 2017. Results: A total of 51 physicians from 24 different states completed the survey. Each response represented a unique institution, the majority of which were public (59%), academic (73%), and contained at least 1 IMCU (65%). Of the IMCUs surveyed, 58% operated as 1 mixed unit that admitted medical, cardiac, and surgical patients as opposed to having separate subspecialty units. Ninety-one percent of units admitted step-down patients from the ICU, but 39% of units accepted a mix of step-up patients, step-down patients, postoperative patients, and patients from the emergency department. Intensivists managed care in 21% of units whereas 36% had no intensivist involvement. Conclusion: Organization practices vary considerably between IMCUs across institutions. The impact of different organization practices on patient outcomes should be assessed.